Peningkatan Kemampuan Menganalisis Unsur Pembangun Puisi melalui Model Problem Based Learning (PBL) Siswa Kelas X SMK Negeri 1 Palembang - Sumarni Sumarni; Missriani Missriani; Sri Wahyu Indrawati (Universitas Batanghari Jambi, 2023)
: This study aims to determine the results of improving the quality of the learning process in the ability to analyze the building blocks of poetry through the problem-based learning model of students for students of SMKN 1 Palembang. To achieve this goal, a class action research was conducted in 2 cycles. The results of the research can be seen from the observation of the learning process in cycle II which shows an increase from cycle I. In cycle II students are more participatory in discussions and when advancing to read poetry and provide feedback from friends who read poetry. Overall, students can take part in learning actively, comfortably and seriously. In addition, teachers have also implemented guidelines for implementing learning to write poetry by applying the Problem Based Learning (PBL) model better. The results of observing the learning process show that the results of the implementation of learning analyze the building blocks of poetry by applying the Problem Based Learning (PBL) model by fulfilling the indicators of the success of the process in this study. In addition, the results of the poetry writing test on the initial average value or pre-cycle, cycle I, and cycle II increased from 48 in the pre-cycle, to 62 in cycle I, and increased significantly to 83 in cycle II. Meanwhile, the percentage of students who met the minimum completeness criteria increased from 15% in the pre-cycle to 56% in cycle I, and increased significantly in cycle II to 91%.